ChemInform Abstract: Intramolecular Thiol—Yne Cyclization as a Novel Strategy for Thioglycal Synthesis. Issue 39 (September 2015) - Corce, Vincent; McSweeney, Lauren; Malone, Aoife; Scanlan, Eoin M.
Abstract This method gives access to thioglycals through a novel intramolecular thiol‐yne cyclization reaction.